Stabilization of peat soil by soil-column technique and settlement of the group columns - Shahidul Islam, M.; Hashim, Roslan (2010)
A field model study was carried out in Klang area of Selengor Dharul Ehsan, Malaysia to observe the settlement of stabilized group peat columns. Peat soil exhibits very low bearing capacity and this soil is not suitable for constructing embankment, highway, building or any other load bearing engineering structure. Large areas of land all over the world are covered by problematic peat soils. The growing demand of space to accommodate new buildings and infrastructures has increased the utilization of soft ground such as peatland. Two sets of test group columns were constructed to stabilize tropical peat by in-situ soil-column with mixing auger and Prebored-premixed method using high setting PFA cement, calcium chloride and siliceous sand as binders. Static load test was performed to observe the settlement of group columns after 28 days of curing time. Computer modelling using PLAXIS software was conducted to compare the load vs. settlement data of group columns. From this study 13.5 mm settlement was observed for the group columns installed by hand mixing and 17.5 mm settlement was found for the mixing auger method. This is due to the fact that proper mixing plays an important role for the achievement of high load carrying capacity of stabilized column.